Impact of temperature variations on RNA content of Freshwater fish Oreochromis mossambicus - Chavan PN; Mali RP (International Journal of Life Sciences, 2017)
The present work deals with the effect of temperature on RNA content of Fresh water fish Oreochromis mossambicus. The fishes were exposed to different temperature such as 20°C, 24°C, 28°C, 32°C, 36°C & 40°C for 24, 48, 72 and 96 hours exposures respectively. The RNA Content were decreased at low temperature and at high temperature as compared to control set. The values of RNA content were expressed in mg/gm wet wt. of tissue and plotted graphically.